The Influence of Product Quality, Service Quality and Promotion on Saving Decision Making in Islamic Banks For UIN North Sumatra Students - M Difach Hazairin Nasution; Rahmat Daim Harahap; Atika, Atika (Yayasan Payungi Smart Madani, 2025)
This study examines the influence of product quality, service quality, and promotion on saving decisions among students at the State Islamic University of North Sumatra (UINSU) within the context of Islamic banking. Using a quantitative approach and purposive sampling, the research involved 100 student respondents. Data were collected via validated questionnaires and analyzed using multiple linear regression, classical assumption tests, and hypothesis testing (t-test and F-test). The findings reveal that all three variables—product quality, service quality, and promotion individually and collectively exert a significant influence on students’ saving decisions. Among them, promotion shows the strongest individual effect. The coefficient of determination indicates that 55.8% of the variance in saving decisions can be explained by these variables. These findings align with the Theory of Planned Behavior (TPB), which suggests that behavioral intentions, influenced by attitudes, subjective norms, and perceived behavioral control, play a central role in decision-making processes. The research also supports the consumer decision-making process and SERVQUAL models, which emphasize the roles of information, evaluation, and service attributes in shaping consumer choices. This study underscores the strategic importance for Islamic banks to enhance their product offerings, service delivery, and promotional efforts, particularly when targeting younger consumers such as university students. By strengthening these areas, Islamic banks can better position themselves in a competitive financial landscape and expand their market share. Ultimately, this research contributes to the growing body of literature on Islamic financial behavior and offers actionable insights for improving student engagement with Sharia-compliant financial services.